Determinants of achieving the minimum clinically important difference for the Incremental Shuttle Walk Test in a cardiac rehabilitation population. (25th November 2020) - Alotaibi, J; Doherty, P; Doherty, P
Abstract:  : The primary aim of this study was to identify the determinants of achieving the minimum clinically important difference (MCID) for the Incremental Shuttle Walk Test (ISWT) in the CR population. The secondary aim was to examine whether achieving MCID in ISWT at the end of the CR programme is associated with the likelihood of patients meeting the physical activity recommendation or whether it is associated with the patients' self-reported physical fitness (Dartmouth COOP tool) at the end of the CR programmme. Method: Routine clinical data related to patients who undertook ISWT as a pre- and post-CR functional capacity assessment were taken from National Audit of Cardiac Rehabilitation (NACR) during the 2013 to 2016 and retrospectively analysed. A sub-analysis was conducted to address the secondary aim. Logistic regression approaches, taking account of potential confounders were constructed. Results: For the main study, data from 9, 786 patients (mean age of 63.9±10.7), 77.5% of whom were male, were analysed. Sixteen determinants for achieving the MCID for ISWT in CR patients were identified. A sub-analysis was also conducted on 7, 950 to address the secondary aim. Patients who achieved the MCID were 30% more likely to meet the physical activity recommendation and 60% more likely to rate themselves positively on the self-reported physical fitness Dartmouth COOP scale. Funding Acknowledgement: Type of funding source: None